The attitude of academic staff towards Bitcoin - Turgut Karabulut; Salim Sercan Sari (Ekonomski Vjesnik, 2022)
Purpose: Bitcoin, the most prominent among cryptocurrencies, is a peer-to-peer (“P2P”) electronic currency and payment system used based on mutual trust. The study aims to measure awareness of Bitcoin, which has recently become popular among investors with its rapidly increasing use. To this end, a questionnaire was applied to the participants to evaluate their opinions and preferences regarding Bitcoin. With this purpose in mind, a questionnaire was applied to the academics of Erzincan Binali Yıldırım University in Turkey.